GAMBARAN PENGETAHUAN PASIEN DIABETES MELITUS TENTANG PENURUNAN KADAR GULA DARAH DENGAN AKTIFITAS FISIK DI RSU ROYAL PRIMA MEDAN TAHUN 2024 - Ince Trisepti Zai; Isabela Buulolo; Elshinta Putri Kristina Zagoto; Sunarti (PT. Hasba Edukasi Mandiri, 2025)
Diabetes is a chronic disease that occurs because the pancreas cannot produce enough insulin (a hormone that regulates blood sugar or glucose), or when the body cannotl effectively use the insulin it produces. The purpose ofl this study is to identify the level ofl knowledge ofl Diabetes Mellitus patients in lowering blood sugar levels with physical activity. This study used quantitative research design using descriptive methods. The population of this study is patients who experience diabetes mellitus in November and December 2023 at Royal Prima Medan Hospital as many as 60 people. The sampling of this study is purposive sampling. The sample of this study amounted to 30 people. The results ofl this study were 30 respondents of Diabetes Mellitus (DM) where the results of respondents' knowledge were good as many as 20 people (66.7%), medium knowledge as many as 7 people (23.3%), and knowledge less as many as 3 people (10.0%). The results of this study show that most Diabetes Mellitus patients have a fairly good understanding of the relationship between physical activity and decreased blood sugar levels. This indicates that education about the benefits of physical activity in managing Diabetes Mellitus can make a positive contribution in increasing patient knowledge.